The Effect Of Irradiation Time and Power Of Led Lights On The Growth Of Red Lettuce (Lactuca sativa L.) In Hydroponic Cultivation Systems - Awangga Kresna Yudatama; Sutarno Sutarno; Eny Fuskhah (University of Prof. Dr. Hazairin, SH, 2023)
This study aims to examine the effect of the treatment of LED light power and irradiation time on the growth of red lettuce plants. The study used a 3 x 3 factorial split plot design with 3 repetitions. The main plot was the irradiation time treatment which consisted of 3 types, 12 hours (L1), 16 hours (L2), and 20 hours (L3) which were carried out at the time of transplanting after the seedling period. Subplots were treated with 3 types of LED lamp power, 10 watt lamp power (D1), 20 watt lamp power (D2), and 30 watt lamp power (D3) which were carried out at the time of transplanting after the seedling period. Parameters observed included plant height, number of leaves, total fresh weight, shoot fresh weight, root fresh weight, root length, and harvest index. The data obtained were analyzed using analysis of variance (ANOVA), then followed by Duncan's Multiple Range Test (DMRT) at the 5% level to see significant differences between treatments. The results showed that the long exposure to light significantly affected the parameters of plant height, total fresh weight, shoot fresh weight, root weight, root length, and harvest index. The treatment of led light power significantly affected the parameters of the number of leaves, total fresh weight, shoot fresh weight, root weight, root length, and harvest index. There is an interaction effect of treatment between irradiation duration and LED light power on parameters of total fresh weight, shoot fresh weight, and root fresh weight.